Incidental gallbladder cancer detected during laparoscopic cholecystectomy: conversion to extensive resection is a feasible choice - Zeng, Di; Wang, Yaoqun; Wen, Ningyuan; Lu, Jiong; Li, Bei; Cheng, Nansheng (Frontiers in Surgery, 2024)
Background: Extensive resection is recommended for patients with incidental gallbladder carcinoma (iGBC) at T1b stage and above. It is unclear whether continuation of laparoscopic extensive-resection (CLR) for patients with intraoperatively detected iGBC (ID-iGBC) is more beneficial to short- and long-term clinical outcomes than with conversion to laparotomy extensive-resection (COR). Methods: This single-centre, retrospective cohort study of patients with iGBC was conducted between June 2006 and August 2021. Patients who underwent immediate extensive-resection for T1b or higher ID-iGBC were enrolled. Propensity score matching (PSM) was used to match the two groups (CLR and COR) of patients, and differences in clinical outcomes before and after matching were analyzed. Result: A total of 102 patients with ID-iGBC were included in this study. 58 patients underwent CLR, and 44 underwent COR. After 1:1 propensity score matching, 56 patients were matched to all baselines. Patients in the COR group had a lower total postoperative complication rate, lower pulmonary infection rate, and shorter operation time than those in the CLR group did. Kaplan-Meier analysis showed that the overall survival rate of patients who underwent CLR was significantly lower than that of patients who underwent COR. Multivariate analysis showed that CLR, advanced T stage, lymph node positivity, and the occurrence of postoperative ascites were adverse prognostic factors for the overall survival of patients. Conclusion: Patients with ID-iGBC who in the COR group had fewer perioperative complications and a better prognosis than the CLR group. For patients with ID-iGBC, conversion to laparotomy extensive-resection appears to be a better choice.